Genetic Diversity and Phylogenetic Analysis of the Sumatran Rhino (Dicerorhinus Sumatrensis) Based on Environmental DNA - Brown, Emily; Tan, Jaden; Roth, Elena (Yayasan Adra Karima Hubbi, 2025)
The Sumatran rhino (Dicerorhinus sumatrensis) remains one of the world’s most critically endangered mammals, and its rapid population decline has raised urgent concerns regarding the species’ genetic viability. Preserving its remaining genetic diversity is essential for designing effective conservation strategies, yet conventional sampling methods are invasive and logistically challenging. This study aims to investigate the genetic diversity and phylogenetic relationships of Sumatran rhinos using environmental DNA (eDNA) collected from peatland wallows and forest water sources across protected habitats. A combination of high-throughput sequencing, mitochondrial marker amplification, and Bayesian phylogenetic modeling was employed to reconstruct lineage structure and assess haplotype variability. The results reveal low overall genetic diversity but clear geographical clustering among northern and southern populations, suggesting historical isolation and limited gene flow. Several rare haplotypes were detected exclusively through eDNA, indicating that non-invasive molecular surveillance can uncover cryptic genetic signatures not captured by traditional methods. These findings highlight the species’ heightened risk of inbreeding and the need for genetically informed translocation or assisted reproduction programs. The study concludes that eDNA-based monitoring provides a robust, scalable tool for guiding long-term conservation management of D. sumatrensis